Assessment of heavy metal contamination in water, sediment and fish from the Jimi Reservoir, Obuasi - Asante, Kwame (2014)
A thesis submitted to the Institute of Distance Learning in partial fulfillment of the requirement for the award of the Master of Science Degree in Environmental Science, 2013